Breadfruit starch-wheat flour noodles: preparation, proximate compositions and culinary properties - Akanbi, Taiknwo O.; Saari, Nazamid; Adebowale, A. A.; Farooq, A.; Olaoye, A. O. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Proximate compositions, culinary and sensory properties of noodles prepared from proportionate combinations of breadfruit starch and wheat flour were investigated. Breadfruit starch (BS) isolated from matured breadfruit (Artocarpus altilis) was used to produce noodles in combination with hard red wheat flour (WF) at a ratio of 100% WF:0% BS, 80% WF:20% BS, 60% WF:40% BS, 40% WF:60% BS, 20% WF:80% BS. The protein, fat, ash, crude fibre and moisture contents of the Breadfruit starch-Wheat flour (BSWF) noodles prepared from the above blends ranged from 0.65 to 10.88%, 0.35 to 3.15%, 1.28 to 2.25%, 1.18 to 1.45% and 4.65 to 5.45%, respectively. The contents of protein, fat, ash and crude fibre increased as the percentage breadfruit starch decreased. However, values of moisture content did not follow the same trend, instead higher values were found for 100% BS:0% WF (5.35%) and 20% BS:80% WF (5.45%). The cooking yield of the BSWF noodles ranged from 21.02 (60% BS:40% WF) to 23.75 g (100% BS:0% WF), cooking loss ranged from 5.49 (20% BS:80% WF) to 9.19% (100% BS:0% WF), while swelling index ranged from 3.1 (20% BS:80% WF) to 3.4 (100% BS:0% WF). Throughout the study, noodles produced from blends of 20% breadfruit starch and 80% wheat flour showed superior proximate, culinary and sensory attributes.